2016
DOI: 10.1021/acscatal.6b00935
|View full text |Cite
|
Sign up to set email alerts
|

Promotional Effects of Cesium Promoter on Higher Alcohol Synthesis from Syngas over Cesium-Promoted Cu/ZnO/Al2O3 Catalysts

Abstract: The promotional effects of a cesium promoter on higher alcohol (C2+OH) synthesis from syngas over Cs2O-Cu/ZnO/Al2O3 catalysts were investigated using a combined experimental and density functional theory (DFT) calculation method. In the presence of a cesium promoter, the C2+OH productivity increases from 77.1 to 157.3 g kgcat –1 h–1 at 583 K due to the enhancement of the initial C–C bond formation. A detailed analysis of chain growth probabilities (CGPs) confirms that initial C–C bond formation is the rate-det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 65 publications
0
56
0
Order By: Relevance
“…The Cu/ZnO based catalysts are widely applied on various catalytic reactions involving synthesis of alcohols . Studies on the phases of Cu‐containing hydroxycarbonates revealed that some precursor phases play important role for the catalytic performance .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cu/ZnO based catalysts are widely applied on various catalytic reactions involving synthesis of alcohols . Studies on the phases of Cu‐containing hydroxycarbonates revealed that some precursor phases play important role for the catalytic performance .…”
Section: Introductionmentioning
confidence: 99%
“…The Cu/ZnO based catalysts are widely applied on various catalytic reactions involving synthesis of alcohols. [1][2][3][4][5][6][7][8] Studies on the phases of Cu-containing hydroxycarbonates revealed that some precursor phases play important role for the catalytic performance. [9][10][11][12][13] The Zn-doped malachite, (Cu 1À x ,Zn x ) 2 (OH) 2 CO 3 , possess homogeneous microstructure, well dispersion of Cu 2 + and Zn 2 + at an atomic level, enhanced metal-oxide interaction after calcination, stability against sintering and high specific surface area and is considered as an effective precursor for industrial Cu/ZnO catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…The copper‐based catalysts with attractive properties have been extensively utilized for the synthesis of methanol and ethanol, for water‐gas shift reaction and for reduction of NO x . Among them, the Cu/ZnO based catalysts have received great attentions due to their remarkable activities for methanol synthesis and reverse water‐gas shift (rWGS) reactions.…”
Section: Introductionmentioning
confidence: 99%
“…A syngas to higher alcohol reaction was reported on Cs promoted Cu‐Zn‐Al catalysts. The authors explained the C‐C bond formation and subsequent chain growth on active sites of Cs . Li promoted Cu‐Zn‐Al catalysts were studied for the CO hydrogenation reaction and the improved alcohol selectivity was attributed to the increased overall basicity of Li‐Cu‐Zn‐Al…”
Section: Introductionmentioning
confidence: 99%